Intelligent transportation system: algorithms and software for road navigation, route guidance and mobile ad hoc network communication - Law, Choi Look (2008)
This report covers the following research topics: centralized multi-constrained Quality of Service (QoS) routing algorithms, MANET test-bed developments, QoS routing protocol for multi-cluster based ad hoc network with mobile backbone, QoS multicast routing protocol for multi-cluster based mobile ad hoc network (MANET), and hierarchical routing algorithms for large scale road networks. For the centralized multi-constrained QoS routing problem, by keeping limited number of non-dominated paths in each node according to a nonlinear path function, we have proposed Limited Path Dijkstra?s Algorithm (LPDA) and the Improved Limited Path Heuristic Algorithm (ILPHA). It is shown that our ILPHA improves the previous Limited Path Heuristic Algorithm (LPHA) significantly, and the heuristic algorithms with dominating area non-linear path function outperform the heuristic algorithms with the max weight based non-linear path function.